Eksistensi Nafs Melalui Terminologi Ilham dalam QS. Al-Syams [91]:7-10: Studi Analisis Filosofis Terhadap Tafsir Al-Mizan Karya Thabathaba'i - Fandi, Fandi Husain; Husain, Fandi; Zakiy, Ahmad Zakiy (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2025)
The Qur'an, which was present in the Arabian Peninsula around the beginning of the 7th century AD, also provides information about the existence of the human soul. However, the entry of Hellenism culture into the Muslim world in the Middle Ages also influenced the perspective of Muslim scholars in interpreting the Qur'an which discusses issues about the soul. This study aims to examine the interpretation of Muhammad Husain Thabathaba'i as a representation of modern mufasir, on QS. al-Syams [91]: 7-10 which contains a description of the existence of the soul. This research uses a qualitative method with the type of library research. The results of this study are, first, Thabathaba'i tends not to limit the meaning of nafs where some mufasir limit it as the soul of Adam as. Secondly, the inspiration given to the human soul by Allah is understood by Thabathaba'i as giving a priori knowledge of abstract values that make humans know for themselves what is good and bad, appropriate and inappropriate. Such an opinion is not the same as that of other scholars who state that the meaning of this verse is that Allah directs man to goodness or piety, nor does it mean teaching the physical form of a practice. Thabathaba'i's interpretation is closer to the views of Ibn 'Ashur and Ibn Atiyah. Thirdly, in interpreting this verse, Thabathaba'i includes various narrations from hadith, atsar, and the opinions of scholars. However, the opinions of scholars that he raises are not only from the Shi'a, but also from the Sunnis such as al-Suyuti and al-Wahidi.